The Lack of Sex, Age, and Anthropometric Diversity in Neck Biomechanical Data - Booth, Gabrielle R.; Cripton, Peter A.; Siegmund, Gunter P. (Frontiers in Bioengineering and Biotechnology, 2021)
Female, elderly, and obese individuals are at greater risk than male, young, and non-obese individuals for neck injury in otherwise equivalent automotive collisions. Developing safety technologies to protect all occupants requires high quality data from a wide range of biomechanical test subjects. Here we sought to quantify the demographic characteristics of the volunteers and post-mortem human subjects (PMHSs) used to create the available biomechanical data for the human neck during impacts. A systematic literature and database search was conducted to identify kinematic data that could be used to characterize the neck response to inertial loading or direct head/body impacts. We compiled the sex, age, height, weight, and body mass index (BMI) for 626 volunteers and 110 PMHSs exposed to 5,431 impacts extracted from 63 published studies and three databases, and then compared the distributions of these parameters to reference data drawn from the neck-injured, fatally-injured, and general populations. We found that the neck biomechanical data were biased toward males, the volunteer data were younger, and the PMHS data were older than the reference populations. Other smaller biases were also noted, particularly within female distributions, in the height, weight, and BMI distributions relative to the neck-injured populations. Increasing the diversity of these parameters in future studies is vital for filling the gaps in the current neck biomechanical data and will provide critical data to address existing inequities in automotive and other safety technologies.